EFEKTIVITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI DESA KAMANGA DUA KECAMATAN TOMPASO KABUPATEN MINAHASA - Mamesah, Frisinthia; PANGKEY, MASJE; KIYAI, BURHANUDDIN (JURNAL ADMINISTRASI PUBLIK, 2018)
This research aims to determine the effectiveness of land and building tax collection in the village of Kamanga Dua, Tompaso Subdistrict. By applying the descriptive-qualitative method, this research uses the types of primary and secondary data, then the data is obtained using interview techniques and field observations. After and collected then analyzed using percentage analysis techniques to see the effectiveness of UN collection then interview data were also analyzed using interactive techniques. The results showed that: (1) Land and Building Tax Collection in Kamanga Dua Village, Tompaso Subdistrict, Minahasa District was categorized in principle "Not yet effective" or successful with an average achievement of 100 percent per year from the target set at 30,150 million rupiah on average per year. (2) The ineffectiveness of UN collection in 2017 is caused by several things, including the transition of the UN management from the central government to the district / city government so that tax officials have not had time to effectively disseminate information to taxpayers and there is an assumption that UN revenue is not fully utilized for the benefit of regional development and even the impression of being misused by certain individuals. It is recommended that in order to achieve the UN acceptance target in the village of Kamanga Dua, Tompaso Subdistrict, Minahasa District, the ability of UN collection officers who have adequate skills is needed, the government is advised to conduct special training for UN collection officers. In order to optimize UN revenues so that they can achieve the set targets, the village government needs to disseminate information to the mandatory UN whenever there are changes to the UN collection policy. Keywords: Effectiveness, Collection of Land and Building Taxes